Interest rate pass-through in the EMU: New evidence from nonlinear cointegration techniques for fully harmonized data - Ansgar Belke; Joscha Beckmann; Florian Verheyen (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This study puts the monetary transmission process in the eurozone between 2003 and 2011 under closer scrutiny. For this purpose, we investigate the interest rate pass-through from money market to various loan rates for up to twelve countries of the European Monetary Union. Applying different cointegration techniques, we first test for a long-run relationship between loan rates and the Euro OverNight Index Average (EONIA). Based on these findings, we allow for different nonlinear patterns for short-run dynamics of loan rates. Our investigation contributes to the literature in mainly two ways. On the one hand, we use fully harmonized data stemming from the ECB's MFI interest rate statistics. In addition, we consider smooth transition models as an extension of conventional threshold models. Our results point to considerable differences in the size of the pass-through with respect to either different loan rates or countries. In the majority of cases, the pass-through is incomplete and the dynamics of loans adjustment are different for reductions and hikes of money market rates.
Keywords: E43; E52; F36; G21; 330; interest rate pass-through; EMU; cointegration; ARDL bounds testing; smooth transition models